PREPAREDNESS OF TECHNICAL VOCATIONAL WORKSHOP LABORATORIES: ITS EFFECT ON STUDENTS’ COMPETENCE AND SKILLS ACQUISITION - Argie Belandres, Elizabeth D. Dioso, Ed. D. (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study examines how students’ competence and skill development in a technical vocational high school are impacted by workshop laboratory readiness. The respondents were 281 students who were officially enrolled in the school year 2022-2023 in Monkayo National High School-Senior High School. This study aims to provide understanding and recommendations for the improvement of workshop laboratories in Technical Vocational Workshop Laboratories for Food and Beverage Services, Bread and Pastry Production and Information and Communications Technology. Correlational methods were conducted and validated through survey questionnaire to measure the level of preparedness of workshop laboratories for Information and Communications technology, food and Beverage Services and Bread and Pastry Production and the level of competence and skill acquisition of students in technical vocational livelihood track. The result reveals that the p-value .05 is less than the correlation coefficient of 0.155 which means that there is no significant relationship between preparedness of ICT laboratory and the level of competence and acquisition of skills of the students. For Food and Beverage, it is clearly indicated in the table that the p-value 0.834 is greater than the correlation coefficient of .059 set at the significant level of 0.05 this means that there is no significant relationship established between the preparedness of the FBS laboratory and the level of competence and skills acquisition of the students. Bread and Pastry Production, the p-value 0.433 is greater than the computed value of .219 set at the significant level of 0.05, this means that there is no significant relationship established between the preparedness of the bread and pastry production laboratory and the level of competence and skills acquisition of the students. The lack of a statistically significant correlation between readiness and competence suggests that learning outcomes are influenced by variables other than the tools and facilities provided in the lab. It is recommended that educators need to check the Training Regulations of Technical Education Skill Development Authority (TESDA) section 3 of the training standards to determine what tools, materials, equipment necessary for the conduct of training the said technical vocational education program.